Harley Davidson Malaysia in a communication perspective - Hashim, Mohd Haizra; Ahmad, Abdul Mu'ati @ Zamri; Osman, Mohd. Nizam; Mohd Yunos, Mohd Yazid (American Research Journals, 2019)
Harley Davidson’s is one of the biggest motorcycle names that is very popular in Malaysia and worldwide. The name has its own appeal among its fans. A Harley Davidson community mostly consists of successful professional groups and entrepreneurs. This biking community is active and it regularly holds meetings as social activities. Some of the members are also distributors of Harley Davidson’s motorcycle parts, sold at reasonable prices due to loyalty and deep enthusiasm in the brand. This study focuses on organisational and visual communication in a Harley Davidson community in Malaysia.